2019
DOI: 10.1002/jper.19-0055
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease, sleep duration, and white blood cell markers in the 2009 to 2014 National Health and Nutrition Examination Surveys

Abstract: Background: Elevated levels of inflammatory biomarkers are consistently associated with chronic conditions, for which periodontitis and sleep are established risk factors. We examined the relationships between periodontitis, hours of sleep and white blood cell (WBC) markers among a nationally representative sample of US adults.Methods: Cross-sectional study using existing demographic, examination, laboratory and questionnaire data on 11,813 participants (5,814 men and 5,999 women, mean age ± SE; range: 52.74 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…The results well confirm our initial theoretical framework (ie, inflammatory hypothesis), which expects the decreased cognitive test scores through exposure to systemic inflammatory factors and leads us to explore the possible mechanisms of the association. The neuroinflammation pathogenesis of dementia gives biological plausibility to these mediating effects (39,40). The periodontal infection leads to leakage of various pathogenic products (ie, host inflammatory factors, pathogenic oral bacteria, and its products) through the gingival epithelium into the bloodstream in the active phases of the disease (6).…”
Section: Discussionmentioning
confidence: 99%
“…The results well confirm our initial theoretical framework (ie, inflammatory hypothesis), which expects the decreased cognitive test scores through exposure to systemic inflammatory factors and leads us to explore the possible mechanisms of the association. The neuroinflammation pathogenesis of dementia gives biological plausibility to these mediating effects (39,40). The periodontal infection leads to leakage of various pathogenic products (ie, host inflammatory factors, pathogenic oral bacteria, and its products) through the gingival epithelium into the bloodstream in the active phases of the disease (6).…”
Section: Discussionmentioning
confidence: 99%
“…Host immune responses determine the severity of tissue destruction during GAgP. Many studies reported elevated leukocytes counts in patients with periodontitis, 3,6,26,27 indicating that GAgP may have effects on markers of systemic inflammation, and the pathogenesis of periodontitis might lead to the increased output of neutrophils. NLR is considered a marker of systematic inflammation, because it is related to many biochemical and cellular activities, and shows correlations with inflammatory markers such as CPR 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal disease is highly prevalent in the United States, with up to 90% of adults reported to have gingivitis and nearly 50% of adults estimated to have periodontitis 1‐3 . The development of periodontal disease is initiated through a host immune response to the oral bacteria present in dental plaque 4,5 .…”
Section: Introductionmentioning
confidence: 99%